Poetry & geography : space and place in post-war poetry - Alexander, Neal; Cooper, David (David Christopher), 1978- (Poetry &--, 2013)
Poetry & Geography examines the rich diversity of geographical imaginations informing post-war and contemporary poetry in Britain and Ireland. Drawing impetus from the spatial turn in the humanities and social sciences, the fourteen essays collected here appraise the significance of ideas of space, place, and landscape for 'mainstream' and 'experimental' poets, post-romantics and neo-modernists alike. Cumulatively, the book's varied articulations of poetry and geography sketch out a series of intersections between language and location, form and environment, sound and space. Poetry's unique capacity to invigorate and expand our vocabularies of site and situation, of our manifold relations with the world outside us, is described and explored. Bringing together fresh, interdisciplinary readings of poets as diverse as Roy Fisher and R.S. Thomas, John Burnside and Thomas Kinsella, Jo Shapcott and Peter Riley, Alice Oswald and Ciaran Carson, Poetry & Geography sketches a topographical map of shared poetic terrains. It contributes to a fertile set of dialogues between literary studies and cultural geography in which the valences of space and place are open to processes of contestation and reimagining. This new collection of critical essays provides readers with a vital set of coordinates in a complex and evolving field. Key themes include: place and identity; literary cartographies; walking as trope and spatial practice; the poetics of edges, margins, and peripheries; landscape, language, and form.